Illness perception and treatment belief among hypertensive patient in medical ward at Hospital Universiti Sains Malaysia - Salleh, Norahidayah (Universiti Sains Malaysia, 2013)
Hypertension is a major public health issue that remains asymptomatic until complications develop. Evidence can be found in the literature that illness perception was associated with treatment belief. Objectives of this study were to determine the association between illness perception and treatment belief among hypertensive patient. This study also determined the association between socio-demographic data and treatment belief. This study was done on 95 hypertensive patients were recruited in wards 7 Utara and 7 Selatan. The Self-Regulation model was used as the theoretical framework of this study. Data were analyzed using Pearson Chi-square test. The results showed specific-necessary belief about medications was not associated with illness perception 0.05). with p-value is 0.175 (ρ/? However, the result in this study found that illness perception was significantly associated with specific-concern belief about medications where p-value is 0.00 (ρ/? 0.05). Certain socio-demographic data were found to be associated with specific-necessary and specific-concern treatment belief. The result of this study showed that specific-necessity treatment belief was associated only with gender and monthly income. Specific-concern treatment belief was found to be associated with age, monthly income and education level. These results suggest that the patient perception of hypertension influenced patients decision on taking medication when they think of side effects and harmful of medication. This also influenced by age, income and knowledge.